Factors Associated with Informed Decisions and Participation in Bowel Cancer Screening among Adults with Lower Education and Literacy. (August 2014) - Smith, Sian K.; Simpson, Judy M.; Trevena, Lyndal J.; McCaffery, Kirsten J.
Background . Making informed decisions about cancer screening involves understanding the benefits and harms in conjunction with personal values. There is little research examining factors associated with informed decision making or participation in screening in the context of a decision aid trial. Objectives . To identify factors associated with informed choice and participation in fecal occult blood testing (FOBT) among lower education populations. Design . Randomized controlled trial of an FOBT decision aid conducted between July and November 2008. Setting . Socioeconomically disadvantaged areas in New South Wales, Australia. Participants . Included 572 adults aged 55 to 64 years with lower education. Measurements . Sociodemographic variables, perceived health literacy, and involvement preferences in decision making were examined to identify predictors of informed choice (knowledge, attitudes, and behavior). Results . Multivariate analysis identified independent predictors of making an informed choice as having higher education (relative risk [RR], 1.49; 95% confidence interval [CI], 1.13–1.95; P = 0.001), receiving the decision aid (RR, 2.88; 95% CI, 1.87–4.44; P < 0.001), and being male (RR, 1.48; 95% CI, 1.11–1.97; P = 0.009). Participants with no confidence in completing forms and poorer self-reported health were less likely to make an informed choice (RR, 0.74; 95% CI, 0.53–1.03; P = 0.05 and RR, 0.57; 95% CI, 0.36–0.89; P = 0.007, respectively). Independent predictors of completing the FOBT were positive screening attitudes, receiving the standard information, preference for making the decision alone, and knowing that screening may lead to false-positive/negative results. Limitations . We did not objectively measure health literacy. Conclusions . Participants with the lowest levels of education had greater difficulties making an informed choice about participation in bowel screening. Alternative methods are needed to support informed decision making among lower education populations.